Post Hospitalization Clinical Quality Outcomes Among US Patients with Schizophrenia Treated with a Long-Acting Injectable or Switched to a New Oral Antipsychotic: A Retrospective Cohort Study - Charmi Patel; Seth Emont; Zhun Cao; Manu Tyagi; Carmela Benson (Adis, Springer Healthcare, 2023)
Abstract Background  Adherence to antipsychotic medication and care discontinuity remain a challenge to healthcare practitioners providing care to patients with schizophrenia. Objective This study used real-world data from a US hospital-based, all-payer database to examine clinical quality measures among patients with schizophrenia initiated on a long-acting injectable (LAI) or switched to a new oral antipsychotic medication (OAP) following a hospitalization. Methods A retrospective cohort study using the PINC AI™ Healthcare Database compared two cohorts of patients with schizophrenia on post-index hospitalization clinical quality and care continuity endpoints. Patients initiated on an LAI (n = 7292) or switched to a new OAP (n = 31,956) during an index hospitalization between April 2017 and April 2020 were included. Propensity score weighting addressed differences in patient, hospital, and clinical characteristics between the two cohorts. Results Patients who initiated an LAI experienced significantly greater adjusted 30-day antipsychotic medication continuation to index therapy, higher rate of 30-day outpatient follow-up care, longer mean time to discontinuation of index therapy, and lower risk of discontinuing their index treatment compared to patients who switched to a new OAP (all p values < 0.001). Probability of 30-day antipsychotic medication continuation was significantly higher for LAI initiators than for patients who switched to a new OAP, even after controlling for patient, clinical, and hospital characteristics (adjusted odds ratio = 1.2, 95% CI 1.1-1.3, p < 0.001). Conclusion Patients who initiated an LAI in a hospital setting experienced better clinical quality and care continuity outcomes compared to patients who were switched to a new OAP. These findings may be useful in identifying solutions to help improve the quality of medication management post-hospital discharge among patients with schizophrenia.